The presence of three portuguese TV news channels (RTP3, SIC Notícias, and TVI24) on Facebook - Rodrigues, Rui (2017)
The growing popularity of social networks, and their impact on the daily lives of consumers, contributed to news organizations marking their presence on different online platforms. In the case of Facebook, a social network that began as a personal space, it has gradually transformed into a content-sharing space (Oeldorf-Hirsch & Sundar, 2015). Nowadays, Facebook is the second most viewed website in Portugal (Alexa, 2016), and therefore, it has become crucial for Portuguese news agencies to be present on this social network. Although television continues to be the main information source in Portugal, social networks, and specifically Facebook, are increasingly important in news consumption by users (ERC, 2015). This new way of news dissemination, as well as the proliferation that these contents reach in social networks, led to news agencies exploiting these new channels, both to attract new audiences, and to redirect users to their own websites (Castillo, El-Haddad, Pfeffer, & Stempeck, 2014). Thus, it is important to understand how, and what kind of content these agencies put on their Facebook channels, as well as the strategies they use to share these same contents. This study aims to understand how the main news channels of Portuguese TV (RTP3, SIC Notícias, and TVI24) manage and use the social network Facebook to share news contents. To this end, the authors collected quantitative data of all posts placed on Facebook between February 8 and February 14 2016. Approximately 1063 posts were collected and analysed from the three Facebook pages. The results indicate that two of the three channels extensively used their Facebook pages to share and target content to their official websites. Regarding the news sources and type of media used, the three Portuguese TV news channels use similar strategies. However, in what concerns the main thematic and quantity of messages per day, as well as the level of redundancy of information, the three channels operate their pages differently.